The Development, Fine Specificity, and Importance of High-Avidity Antibodies to VAR2CSA in Pregnant Cameroonian Women Living in Yaoundé, an Urban City - Vanda, Koko; Bobbili, Naveen; Matsunaga, Masako; Chen, John J.; Salanti, Ali; Leke, Rose F. G.; Taylor, Diane Wallace (Frontiers in Immunology, 2021)
When pregnant women are infected with Plasmodium falciparum, they produce antibodies (Abs) to VAR2CSA, a ligand that binds to placental chondroitin sulfate A causing placental malaria (PM). Antibodies (Abs) to VAR2CSA are associated with improved pregnancy outcomes. Antibody avidity is a surrogate marker for the extent of affinity maturation of B cells. Little is known about the development of high avidity Abs to VAR2CSA for women living in urban African cities. Therefore, this study sought to determine: i) if high avidity Abs to full-length VAR2CSA (FV2) increase with gravidity in women in Yaoundé, Cameroon exposed to ~ 0.3-1.1 infectious mosquito bites per month, ii) if high avidity Ab to FV2 are directed against a specific region of VAR2CSA, and iii) if having high avidity Abs to FV2 improve pregnancy outcomes. Plasma samples collected at delivery from 695 women who had Ab to FV2 were selected. Ab levels and the Avidity Index (AI), defined as the percent Ab remaining bound to FV2 after treatment with 3M NH4SCN, were determined. Similar Ab levels to FV2 were present in women of all gravidities (G1 through 6+) (p=0.80), except significantly lower levels were detected in PM- primigravidae (p <0.001). Mean Ab avidities increased between the first and second pregnancies (p<0.001) and remained stable thereafter (p=0.51). These results suggest that B cell clonal expansion began during the first pregnancy, with clonal selection primarily occurring during the second. However, high avidity Abs were detected in only 46% of the women, even though they had Ab to FV2. When plasma from 107 Cameroonian women was tested against 8 different regions of FV2, high avidity Ab were predominately restricted to DBL5 with mean AI of 50 compared to AI <25 of the other domains. Overall, the significance of high avidity Ab was modest, since the birthweight of babies born to women (n=294) with evidence of affinity maturation was slightly heavier (+115 grams) than those born to women (n = 349) without affinity maturation. These results suggest that a vaccine that induces a more robust Ab response against multiple domains could be beneficial for women residing in urban areas.